Dry sliding wear behaviour of talc-reinforced UHMWPE composite for implant application - Boon, Peng Chang; Hazizan Md Akil,; Ramdziah bt Md Nasir, (Universiti Kebangsaan Malaysia, 2015)
As of today, ultra-high molecular weight polyethylene (UHMWPE) is a thermoplastic material normally used as bearing components for human joint replacements. However, formation of wear debris from UHMWPE after certain service periods may cause adverse effects which remain as unresolved issues. In this study, mechanical and dry sliding wear properties of UHMWPE reinforced with different loading of talc particles were investigated. The wear test was carried out using Ducom TR-20 pin-on-disc tester at different pressure velocity (pv) factors under dry sliding conditions. The worn surfaces and transfer films of pure UHMWPE and talc/UHMWPE composites were observed under scanning electron microscope (SEM). The experimental results showed that the microhardness increased with the increase of talc loadings in UHMWPE. The 20 wt. % talc/UHMWPE composites showed a 17% increment in microhardness as compared with pure UHMWPE. The dry sliding wear behaviour of UHMWPE was also improved upon the reinforcement of talc. The wear rate of UHMWPE decreased after incorporation of talc particles. The coefficient of friction (COF) increased slightly under low pv conditions. At high pv conditions, the COF decreased in values with increasing talc loadings. The improvement in wear behaviour may be attributed to the increase in load-carrying capacity and surface hardness of the talc/UHMWPE composites. SEM micrographs on worn surfaces showed that plastic deformation and grooving wear were dominant for UHMWPE. The plastic deformation and grooving wear were reduced upon the reinforcement of talc particles. The talc/UHMWPE composites produced smoother and uniform transfer films as compared to pure UHMWPE.